Three-layer breather valve composite membrane as well as preparation method and application thereof

By adopting a three-layer structure breathing valve composite diaphragm, including polymer sheet layer, fluoroelastic composite material layer and fiber composite polymer interlayer, the problem of high leakage amount of existing breathing valve diaphragm is solved, and the effect of low leakage amount and high temperature resistance is achieved.

CN119590053AActive Publication Date: 2025-03-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311166922.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-11
Publication Date
2025-03-11
Estimated Expiration
2043-09-11

AI Technical Summary

Technical Problem

The existing respiratory valve diaphragm has high leakage in large nominal diameter breathing valves, which poses a high safety risk, and is difficult to meet the leakage requirements of international standards.

Method used

A three-layer breathing valve composite diaphragm is used, including a polymer sheet layer, a fluoroelastic composite material layer and a fiber composite polymer interlayer. By improving the performance of the composite fluoroelastic diaphragm, the leakage amount is significantly reduced and the high temperature resistance is improved.

Benefits of technology

It significantly reduces the leakage of the large nominal diameter breathing valve, meets or is lower than international standards, and improves the high temperature resistance and enhances the safety and reliability of the breathing valve.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119590053A_ABST
    Figure CN119590053A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of breather valve sealing, and discloses a three-layer breather valve composite membrane and a preparation method and application thereof. The composite membrane comprises a polymer sheet layer, a fluororubber composite material layer and a fiber composite polymer interlayer located between the polymer sheet layer and the fluororubber composite material layer, and the thickness of the polymer sheet layer is 0.1-1 mm; the fluororubber composite material layer is prepared from a raw material composition containing fluororubber, inorganic filler, an acid acceptor, a vulcanizing agent, a release agent and a coloring agent. When the temperature is 20 DEG C and the opening pressure of the storage tank breather valve is 0.75 times, the leakage rate of the composite diaphragm provided by the invention is as follows: the maximum leakage rate of the breather valve diaphragm with the nominal diameter of 150mm is as low as 0.0010 m < 3 > per hour, and the maximum leakage rate of the breather valve diaphragm with the nominal diameter of 200mm is as low as 0.0028 m < 3 > per hour, which is far lower than the leakage rate related standard of the existing breather valve at home and abroad; the high-temperature-resistant performance is excellent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of breathing valve sealing, and in particular to a three-layer breathing valve composite diaphragm and a preparation method and application thereof. Background Art

[0002] A breathing valve is a valve that not only ensures that the storage tank space is isolated from the atmosphere within a certain pressure range, but can also communicate with the atmosphere (breathe) when the pressure exceeds or falls below this pressure range. Its function is to prevent the storage tank from being damaged due to overpressure or vacuum, and at the same time reduce the evaporation loss of the storage medium. Setting a breathing valve can not only reduce the gas emission in the tank, thereby reducing the pollution to the atmosphere, but also prevent the storage tank from being damaged due to overpressure or instability due to ultra-vacuum, which plays a certain role in promoting safety and environmental protection.

[0003] At present, the design and research of breathing valve products in China mainly focuses on the gas flux above the opening pressure, while the gas leakage in the leakage range from 0.75 times the opening pressure to below the opening pressure of the breathing valve has not received much attention. In fact, with the development trend of centralization and large-scale development of storage tank areas, the gas leakage that has been ignored by people is very likely to lead to an increase in the concentration of flammable gases in the tank area, and increase the risk of fire and explosion. For this reason, the American Petroleum Institute (API) clearly stipulates in its breathing valve standard API Std2000 that the maximum leakage of breathing valves with a nominal diameter less than 150mm shall not exceed 0.014m per hour. 3 For breathing valves with a nominal diameter greater than 200 mm, the maximum leakage per hour shall not exceed 0.142 m 3 The most stringent international standard for leakage is the standard in some regions (enterprises) of Germany, which requires that the maximum leakage of breathing valves with a nominal diameter less than 150mm should not exceed 0.0017m per hour. 3 For breathing valves with a nominal diameter greater than 200 mm, the maximum leakage per hour shall not exceed 0.0045 m 3 . At present, the research and development of breathing valves in China mainly focuses on mechanical structures. However, due to the repeated opening and closing of the breathing valve during use, coupled with the large amount of corrosive components in the oil and gas, the mechanical seal is very easy to be damaged and fail, resulting in increased leakage. Therefore, a reasonable mechanical structure and an efficient sealing rubber diaphragm can be combined to achieve a long-term low leakage of the breathing valve. However, due to the limitations of diaphragm materials, my country's breathing valve industry standard SY / T0511-2010 stipulates that for breathing valves with a nominal diameter of less than 150mm, the maximum leakage per hour shall not exceed 0.04m 3 For breathing valves with a nominal diameter greater than 200 mm, the maximum leakage per hour shall not exceed 0.4 m 3The leakage volume is significantly higher than the current international standards. On the one hand, the high leakage volume increases the safety risk of my country's petrochemical storage tank area, which is a huge hidden danger to people's stable life. On the other hand, it also limits my country's domestic independent development path in the field of petrochemical oil and gas storage. Summary of the invention

[0004] The purpose of the present invention is to overcome the problem that the conventional breathing valve diaphragm (gasket) used for breathing valves with large nominal diameters has high leakage and high safety risks in the prior art, and to provide a three-layer breathing valve composite diaphragm and its preparation method and application. The present invention can significantly reduce the leakage of breathing valves of storage tanks with large nominal diameters by improving the performance of the composite fluororubber diaphragm, and has excellent high temperature resistance.

[0005] In order to achieve the above-mentioned purpose, the present invention provides a three-layer breathing valve composite diaphragm on one hand, wherein the composite diaphragm includes a polymer sheet layer, a fluororubber composite material layer, and a fiber composite polymer interlayer located between the polymer sheet layer and the fluororubber composite material layer, wherein the thickness of the polymer sheet layer is 0.1 to 1 mm; the fluororubber composite material layer is made of a raw material composition containing fluororubber, inorganic filler, acid absorber, vulcanizer, release agent and colorant.

[0006] Preferably, the polymer sheet material in the polymer sheet layer is selected from one or more of polyetheretherketone, polytetrafluoroethylene and polyimide.

[0007] Preferably, the fiber composite polymer sheet forming the fiber composite polymer interlayer is selected from one or more of aramid polytetrafluoroethylene composite rubber, aramid polyimide rubber, glass fiber polyimide rubber, carbon fiber polyimide rubber and ceramic fiber polyimide rubber.

[0008] Preferably, the fiber composite polymer interlayer has a thickness of 0.1 to 0.5 mm.

[0009] Preferably, in the raw material composition, the fluororubber is type 26 fluororubber and / or type 246 fluororubber.

[0010] Preferably, in the raw material composition, the inorganic filler is selected from one or more of white carbon black, calcium silicate, magnesium silicate, aluminum silicate, calcium carbonate, barium sulfate, diatomaceous earth, graphite, silicon nitride and boron nitride.

[0011] Preferably, in the raw material composition, the acid absorber is selected from one or more of magnesium oxide, calcium oxide, zinc oxide and calcium hydroxide.

[0012] Preferably, in the raw material composition, the vulcanizing agent is selected from one or more of N,N'-dicinnamaldehyde-1,6-hexanediamine, 2,2-(4-hydroxyphenyl)hexafluoropropane, diisopropylbenzene peroxide and 2,5-dimethyl-2,5-di-tert-butylhexane peroxide.

[0013] Preferably, in the raw material composition, the release agent is selected from one or more of zinc stearate, ammonium stearate and paraffin.

[0014] Preferably, in the raw material composition, the colorant is selected from one or more of iron red, colloidal graphite and carbon black.

[0015] Preferably, in the raw material composition, the weight ratio of the fluororubber, the inorganic filler, the acid absorber, the vulcanizing agent, the release agent and the colorant is 100:10-60:0.001-20:0.001-5:0.2-2:0.001-3.

[0016] Preferably, the raw material composition further contains a vulcanization accelerator.

[0017] Preferably, the weight ratio of the fluororubber to the vulcanization accelerator is 100:0.001-2.

[0018] Preferably, the vulcanization accelerator is selected from benzyltriphenylphosphonium chloride and / or triallyl isocyanurate.

[0019] Preferably, the thickness ratio of the polymer sheet layer to the fluororubber composite material layer is 1:1-4.

[0020] A second aspect of the present invention provides a method for preparing the three-layer breathing valve composite diaphragm, the method comprising:

[0021] (1) kneading the raw material composition, and then refining the obtained product multiple times to obtain a fluororubber composite material;

[0022] (2) Placing the fiber composite polymer sheet between the polymer sheet and the fluororubber composite material, and then performing thermal bonding and vulcanization to obtain a composite membrane.

[0023] Preferably, in step (1), the mixing conditions include: temperature of 50 to 80° C., time of 15 to 60 min, and rotation speed of 20 to 60 rpm.

[0024] Preferably, in step (1), the refining conditions include: a temperature of 100 to 140° C., a refining number of 10 to 30 times, and a roller distance of 0.2 to 4 mm.

[0025] Preferably, in step (2), the conditions for thermal bonding include: a temperature of 150 to 160° C. and a time of 1 to 10 min.

[0026] Preferably, in step (2), the vulcanization conditions include: temperature of 180-240° C. and time of 8-24 hours.

[0027] The third aspect of the present invention provides a three-layer breathing valve composite membrane prepared by the method described above.

[0028] A fourth aspect of the present invention provides a composite diaphragm as described above or use of the composite diaphragm as described above as a sealing material for a breathing valve.

[0029] The composite diaphragm provided by the present invention includes a polymer sheet layer of specific thickness and a specific fluororubber composite material layer, and a fiber composite polymer interlayer is provided between the polymer sheet layer and the fluororubber composite material layer. The three-layer composite diaphragm having this feature has an excellent yield deformation in the leakage range from above 0.75 times the opening pressure of the breathing valve to below the opening pressure, thereby reducing the leakage of the breathing valve with a large nominal diameter. At the same time, the breathing valve composite diaphragm prepared by the present invention has excellent high temperature resistance.

[0030] Furthermore, the composite diaphragm provided by the present invention has a leakage rate of 0.75 times the opening pressure of the tank breathing valve at a temperature of 20°C: the maximum leakage rate of the diaphragm used for the breathing valve with a nominal diameter of 150mm or less is as low as 0.0010m per hour. 3 The maximum leakage of the breathing valve diaphragm with a nominal diameter of 200mm is as low as 0.0028m per hour. 3 , which is far lower than the existing domestic and foreign standards for the leakage of breathing valves. In the present invention, the "nominal diameter" refers to the nominal diameter of the breathing valve connection flange. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 The present invention is a flow chart of preparing a three-layer breathing valve composite membrane. DETAILED DESCRIPTION

[0032] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.

[0033] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0034] A first aspect of the present invention provides a three-layer breathing valve composite diaphragm, the composite diaphragm comprising a polymer layer, a fluororubber composite material layer, and a fiber composite polymer interlayer located between the polymer layer and the fluororubber composite material layer.

[0035] In the present invention, the polymer sheet layer supports the composite diaphragm and is located on one side of the valve disc of the breathing valve when in use, so as to prevent the edge of the diaphragm from sagging due to being too soft, thereby causing air leakage in the breathing valve. Lubricants and thermal conductors are added during pretreatment of the polymer sheet, so the polymer sheet has good lubricity, thermal conductivity and friction resistance. The fluororubber composite material layer has good elasticity and appropriate elastic deformation. When in use, it is located on one side of the valve seat of the breathing valve, so that the breathing valve has excellent sealing performance. The fiber composite polymer interlayer located in the middle helps to maintain the dimensional stability of the composite diaphragm and increase the deformation recovery ability. Compounding the polymer sheet layer, the fiber composite polymer interlayer and the fluororubber composite material layer can significantly reduce the leakage of breathing valves with large nominal diameters and improve high temperature resistance.

[0036] In the present invention, the thickness of the polymer sheet layer should be appropriate. If it is too thick, the membrane will be hard as a whole, and the surface will be uneven and concave, and the effect of reducing the leakage of the breathing valve cannot be achieved.

[0037] In the present invention, the thickness of the polymer sheet is 0.1-1 mm. In a specific embodiment, the thickness of the polymer sheet can be 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 0.6 mm, 0.7 mm, 0.8 mm, 0.9 mm or 1 mm.

[0038] In the present invention, the polymer sheet refers to a material forming a polymer sheet. In a specific embodiment, the polymer sheet forming the polymer sheet can be a material well known to those skilled in the art. In a preferred embodiment, the polymer sheet in the polymer sheet can be selected from one or more of polyetheretherketone (PEEK), polytetrafluoroethylene (PTFE) and polyimide (PI).

[0039] In a specific embodiment, the polymer sheet layer is entirely formed of polymer sheets, and the polymer sheets need to be pre-treated before use. The pre-treatment includes: adding lubricants and thermal conductive agents to enhance the lubricity, thermal conductivity and anti-friction properties, and performing surface treatment on the polymer sheets.

[0040] In the present invention, specifically, the fiber composite polymer interlayer is formed by a fiber composite polymer sheet; the fiber composite polymer sheet refers to the material forming the fiber composite polymer interlayer. In the present invention, in a specific embodiment, the fiber composite polymer sheet forming the fiber composite polymer interlayer can be a material well known to those skilled in the art. In a preferred embodiment, the fiber composite polymer sheet forming the fiber composite polymer interlayer can be selected from one or more of aramid polytetrafluoroethylene composite rubber, aramid polyimide rubber, glass fiber polyimide rubber, carbon fiber polyimide rubber and ceramic fiber polyimide rubber.

[0041] In a preferred embodiment, the thickness of the fiber composite polymer interlayer can be 0.1 to 0.5 mm. If the thickness of the fiber composite polymer interlayer is too large, the elasticity of the composite diaphragm will be significantly reduced; if the thickness of the fiber composite polymer interlayer is too small, it will not be able to increase the effect of deformation recovery; too large or too small will affect the leakage of the breathing valve.

[0042] The inventors have found through research that in the present invention, the composite diaphragm composed of a fluororubber composite material layer prepared from raw materials containing fluororubber, a fiber composite polymer interlayer and the polymer sheet layer can be used as a breathing valve sealing material to significantly reduce the leakage of a breathing valve with a large nominal diameter.

[0043] In the present invention, the fluororubber composite material layer is prepared from a raw material composition containing fluororubber, inorganic filler, acid absorbent, vulcanizing agent, mold release agent and colorant. The fluororubber composite material layer is obtained by mixing, refining, thermal bonding and vulcanization of the raw material composition.

[0044] In the present invention, the fluororubber can be any fluororubber known in the art, as long as it can maintain the gasket shape and mechanical strength in an oil, acid or alkali environment. In a specific embodiment, in the raw material composition, the fluororubber can be 26-type fluororubber and / or 246-type fluororubber.

[0045] In the present invention, the inorganic filler can be a conventional choice in the art, as long as it can fill the rubber. In a preferred embodiment, in order to make the diaphragm have a good yield deformation in the leakage range of 0.75 times the opening pressure of the breathing valve to below the opening pressure, and further reduce the leakage of the breathing valve, in the raw material composition, the inorganic filler is selected from one or more of white carbon black, calcium silicate, magnesium silicate, aluminum silicate, calcium carbonate, barium sulfate, diatomaceous earth, graphite, silicon nitride and boron nitride.

[0046] In the present invention, the acid absorber refers to an additive capable of absorbing acidic substances released during the rubber preparation process. The acid absorber can be a conventional choice in the art, as long as it can absorb acidic substances released during the rubber preparation process. In a preferred embodiment, in the raw material composition, the acid absorber is selected from one or more of magnesium oxide, calcium oxide, zinc oxide and calcium hydroxide.

[0047] In the present invention, the vulcanizing agent can be a conventional choice in the art. In a specific embodiment, in the raw material composition, the vulcanizing agent is selected from one or more of N,N'-biscinnamaldehyde-1,6-hexanediamine, 2,2-(4-hydroxyphenyl)hexafluoropropane, diisopropylbenzene peroxide and 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane.

[0048] In the present invention, the release agent may be a release agent well known to those skilled in the art. In a specific embodiment, in the raw material composition, the release agent is selected from one or more of zinc stearate, ammonium stearate and paraffin.

[0049] In the present invention, the colorant can be a colorant known to those skilled in the art, as long as it can color the composite film. In a specific embodiment, in the raw material composition, the colorant is selected from one or more of iron red, colloidal graphite and carbon black.

[0050] In the present invention, in order to improve the yield recovery performance of the fluororubber composite material layer and thus reduce the leakage of the breathing valve, it is necessary to reasonably control the amount of the fluororubber, the inorganic filler, the acid absorber, the vulcanizer, the release agent and the colorant.

[0051] In the present invention, in a specific embodiment, in the raw material composition, the weight ratio of the fluororubber, the inorganic filler, the acid absorber, the vulcanizing agent, the release agent and the colorant can be 100:10-60:0.001-20:0.001-5:0.2-2:0.001-3, for example, 100:10:0.28:0.15:1.89:1.54, 100:60:0.5 4:2.16:1.55:2.05、100:20:10:2.5:1.6:2.5、100:50:10.8:3.85:0.88:2.35、100:30:0.2:0.1:1:1.5、100:40:10.5:1.25:1.58:0.55、100:10:0.2:0.1:1:1.5、100:60:20:5:2:3.

[0052] In the present invention, whether to add a vulcanization accelerator to the raw materials for preparing the fluororubber composite material layer is selected according to actual needs. In a specific embodiment, the raw material composition also contains a vulcanization accelerator. In a preferred embodiment, the weight ratio of the fluororubber to the vulcanization accelerator is 100:0.001 to 2, for example, 100:0.001, 100:0.1, 100:0.2, 100:0.5, 100:0.6, 100:0.7, 100:0.8, 100:0.9 or 100:1. Specifically, the vulcanization accelerator is selected from benzyltriphenylphosphonium chloride and / or triallyl isocyanurate.

[0053] In the invention, in order to meet the basic use requirements, the thickness of the polymer sheet and the fluororubber composite material layer need to meet a certain relationship. In a specific embodiment, the thickness of the fluororubber composite material layer is equivalent to the thickness of the polymer sheet, or the thickness of the fluororubber composite material layer is thicker than the polymer sheet. In a preferred embodiment, the ratio of the thickness of the polymer sheet to the fluororubber composite material layer is 1:1 to 4, for example, 1:1, 1:1.2, 1:1.4, 1:1.5, 1:1.6, 1:1.8, 1:2, 1:2.2, 1:2.4, 1:2.5, 1:2.6, 1:2.8, 1:3, 1:3.2, 1:3.4, 1:3.6, 1:3.8 or 1:4.

[0054] The second aspect of the present invention provides a method for preparing the three-layer breathing valve composite membrane described in the first aspect, such as Figure 1 As shown, the method includes:

[0055] (1) kneading the raw material composition, and then refining the obtained product multiple times to obtain a fluororubber composite material;

[0056] (2) Placing the fiber composite polymer sheet between the polymer sheet and the fluororubber composite material, and then performing thermal bonding and vulcanization to obtain a composite membrane.

[0057] The method of the present invention first prepares a fluororubber composite material by mixing and refining, then places a fiber composite polymer sheet between a polymer sheet and the fluororubber composite material, and thermally bonds and vulcanizes the three to bond the fluororubber composite material, the fiber composite polymer sheet and the polymer sheet to obtain a three-layer composite membrane including a polymer sheet layer, a fluororubber composite material layer, and a fiber composite polymer interlayer located between the polymer sheet layer and the fluororubber composite material layer.

[0058] In the present invention, the mixing process can be carried out according to conventional operations in the art. In a preferred embodiment, in step (1), the mixing temperature can be 50 to 80°C, such as 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C. In a preferred embodiment, in step (1), the mixing time can be 15 to 60 minutes, such as 15 minutes, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, 45 minutes, 50 minutes, 55 minutes or 60 minutes. In a preferred embodiment, in step (1), the mixing speed can be 20 to 60 rpm, such as 20 rpm, 25 rpm, 30 rpm, 35 rpm, 40 rpm, 45 rpm, 50 rpm, 55 rpm or 60 rpm. In the present invention, the mixing is carried out using a mixer of the BL-6175-B model of Baisheng Company.

[0059] In the method of the present invention, the refining process can be carried out according to conventional operations in the art. In a preferred embodiment, in step (1), the refining temperature is 100-140°C, such as 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C or 140°C. In a preferred embodiment, in step (1), the number of refining times is 10 times, 15 times, 20 times, 25 times or 30 times. In a preferred embodiment, the roller spacing is 0.2-4mm, such as 0.2mm, 0.5mm, 1mm, 1.5mm, 2mm, 2.5mm, 3mm, 3.5mm or 4mm. In the present invention, the refining is carried out using a mixer of model MRM480 ​​of Meissen Machinery Company. In the present invention, refining once means that the roller rolls one circle from the mixed raw material.

[0060] In the method of the present invention, the thermal bonding may be a conventional choice in the art. In a preferred embodiment, in step (2), the thermal bonding temperature is 150-160°C, such as 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C. In a preferred embodiment, in step (2), the thermal bonding time is 1-10 min, such as 1 min, 2 min, 3 min, 4 min, 5 min, 6 min, 7 min, 8 min, 9 min or 10 min.

[0061] In the method of the present invention, the vulcanization process can be carried out according to conventional operations in the art. In order to make the diaphragm have a good yield deformation in the leakage interval from above 0.75 times the opening pressure of the breathing valve to below the opening pressure, and further reduce the leakage of the breathing valve, the vulcanization conditions can be controlled within an appropriate range. In a preferred embodiment, in step (2), the vulcanization temperature can be 180 to 240°C, for example, 180°C, 190°C, 200°C, 210°C, 220°C, 230°C or 240°C. In a preferred embodiment, in step (2), the vulcanization time is 8 to 24h. For example, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h.

[0062] In a specific embodiment, the method for preparing the three-layer breathing valve composite membrane comprises the following steps:

[0063] (1) Preparation of fluororubber composite material: fluororubber, inorganic filler, acid absorber, vulcanizing agent, mold release agent and colorant are mixed at a temperature of 50 to 80°C, a time of 15 to 60 min, a rotation speed of 20 to 60 rpm, and a weight ratio of the fluororubber, inorganic filler, acid absorber, vulcanizing agent, mold release agent and colorant of 100:10 to 60:0.001 to 20:0.001 to 5:0.2 to 2:0.001 to 3, and then the obtained product is refined for 10 to 30 times, the refining temperature is 100 to 140°C, and the roller distance is 0.2 to 4 mm, to obtain a fluororubber composite material;

[0064] (2) Preparation of composite membrane:

[0065] A fiber composite polymer sheet with a thickness of 0.1 to 0.5 mm is placed between a polymer sheet with a thickness of 0.1 to 1 mm and the fluororubber composite material, and then thermally bonded at a temperature of 150 to 160° C. for 1 to 10 minutes, and then vulcanized at a temperature of 180 to 240° C. for 8 to 24 hours to obtain a composite membrane.

[0066] In another specific embodiment, the method for preparing the three-layer breathing valve composite membrane comprises the following steps:

[0067] (1) Preparation of fluororubber composite material: fluororubber, inorganic filler, acid absorber, vulcanizing agent, mold release agent, colorant and vulcanization accelerator are mixed at a temperature of 50 to 80° C., a time of 15 to 60 min, a rotation speed of 20 to 60 rpm, and a weight ratio of the fluororubber, inorganic filler, acid absorber, vulcanizing agent, mold release agent and colorant of 100:10 to 60:0.001 to 20:0.001 to 5:0.2 to 2:0.001 to 3:0.001 to 2, and then the obtained product is refined for 10 to 30 times, the refining temperature is 100 to 140° C., and the roller distance is 0.2 to 4 mm, to obtain a fluororubber composite material;

[0068] (2) Preparation of composite membrane:

[0069] A fiber composite polymer sheet with a thickness of 0.1 to 0.5 mm is placed between a polymer sheet with a thickness of 0.1 to 1 mm and the fluororubber composite material, and then thermally bonded at a temperature of 150 to 160° C. for 1 to 10 minutes, and then vulcanized at a temperature of 180 to 240° C. for 8 to 24 hours to obtain a composite membrane.

[0070] The third aspect of the present invention provides a super three-layer breathing valve composite diaphragm prepared by the method described above. The breathing valve composite diaphragm prepared by the method described in the present invention has low valve leakage and good high temperature resistance.

[0071] The fourth aspect of the present invention provides the use of the composite diaphragm described in the first aspect or the composite diaphragm described in the third aspect as a breathing valve sealing material.

[0072] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.

[0073] In the present invention, the fluororubber 246 is purchased from LG Company of South Korea, with a density of 1.5 g / cm 3 , tensile strength 450kg / cm 2 The fluororubber 26 was purchased from Shandong Huaxia Shenzhou Company, and the physical parameters were 1.8g / cm 3 Tensile strength 135kg / cm 2 .

[0074] In the present invention, the aramid polytetrafluoroethylene composite rubber was purchased from Zhejiang Jusheng Fluorine Chemical Co., Ltd., with a density of 2.1 g / cm 3 ; Aramid polyimide rubber was purchased from Suzhou Yingchuan New Material Technology, density 1.9g / cm 3 ; Glass fiber polyimide rubber purchased from EMS, Switzerland, density 1.4g / cm 3; Carbon fiber polyimide rubber purchased from DowDuPont, density 1.4g / cm 3 ; Ceramic fiber polyimide rubber was purchased from Ceramic fiber polyimide rubber, density 1.42g / cm 3 .

[0075] Example 1

[0076] (1) Preparation of fluororubber composite materials:

[0077] Fluororubber (10 kg of fluororubber 246), inorganic filler (6 kg of aluminum silicate), acid absorber (1 kg of calcium oxide), vulcanizing agent (0.2 kg of N,N'-biscinnamaldehyde-1,6-hexanediamine), mold release agent (0.02 kg of zinc stearate) and colorant (0.3 kg of colloidal graphite) are added into a mixer for mixing at a speed of 60 rpm, a temperature of 60°C and a time of 15 min; then the obtained product is refined 10 times at a roller distance of 0.2 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0078] (2) Preparation of composite membrane:

[0079] A 0.5 mm thick aramid polytetrafluoroethylene composite rubber sheet is placed on a 0.1 mm thick PEEK polymer sheet, and then the fluororubber composite material is spread on the aramid polytetrafluoroethylene composite rubber sheet and thermally bonded at a temperature of 160°C for a bonding time of 1 min to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 8 h to obtain a composite diaphragm A1 including a 0.2 mm fluororubber composite layer, a 0.1 mm PEEK polymer layer, and a 0.5 mm aramid polytetrafluoroethylene composite rubber interlayer between the PEEK polymer layer and the fluororubber composite layer.

[0080] Example 2

[0081] (1) Preparation of fluororubber composite materials:

[0082] Fluororubber (10 kg of fluororubber 26), inorganic filler (0.5 kg of white carbon black, 0.3 kg of calcium silicate, 0.1 kg of magnesium silicate and 0.1 kg of boron nitride), acid absorber (1 kg of magnesium oxide), vulcanizing agent (0.5 kg of N,N'-biscinnamaldehyde-1,6-hexanediamine), mold release agent (0.02 kg of paraffin wax) and colorant (0.2 kg of iron red) are added into a mixer for mixing, wherein the mixing speed is 20 rpm, the temperature is 80°C and the time is 60 min; then the obtained product is refined 20 times with a roller distance of 2 mm and a roller temperature of 100°C to obtain a fluororubber composite material;

[0083] (2) Preparation of composite membrane:

[0084] A 0.1 mm thick aramid polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the aramid polyimide rubber sheet and thermally bonded at a temperature of 150°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 180°C for 24 hours to obtain a composite diaphragm A2 including a 2 mm fluororubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.1 mm aramid polyimide rubber interlayer between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0085] Example 3

[0086] (1) Preparation of fluororubber composite materials:

[0087] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium carbonate, 1 kg of diatomaceous earth, 0.5 kg of calcium silicate and 0.1 kg of graphite), acid absorbent (1 kg of zinc oxide), vulcanizing agent (0.02 kg of 2,2-(4-hydroxyphenyl)hexafluoropropane and 0.02 kg of benzyltriphenylphosphonium chloride), mold release agent (0.02 kg of ammonium stearate) and colorant (0.03 kg of iron oxide red) were added into a mixer for mixing, and the mixing speed was 30 rpm, the temperature was 70°C, and the time was 40 min; then the obtained product was refined 30 times, the roller distance was 4 mm, and the roller temperature was 120°C, to obtain a fluororubber composite material;

[0088] (2) Preparation of composite membrane:

[0089] A 0.3 mm thick glass fiber polyimide rubber sheet is placed on a 1 mm thick PI polymer sheet, and then the fluororubber composite material is spread on the glass fiber polyimide rubber sheet and thermally bonded at a temperature of 150°C for 5 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 200°C for 16 hours to obtain a 4 mm thick fluororubber composite material layer, a 1 mm thick PI polymer sheet layer, and a 0.3 mm thick glass fiber polyimide rubber sandwich composite diaphragm A3 located between the PI polymer sheet layer and the fluororubber composite material layer.

[0090] Example 4

[0091] (1) Preparation of fluororubber composite materials:

[0092] Fluororubber (10 kg of fluororubber 26), inorganic filler (4 kg of aluminum silicate, 1 kg of barium sulfate, 0.05 kg of silicon nitride and 0.2 kg of graphite), acid absorbent (1 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of diisopropylbenzene peroxide), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.02 kg of paraffin wax) and colorant (0.2 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 40 rpm, the temperature is 65° C. and the time is 30 min; then the obtained product is refined 30 times, the roller distance is 0.5 mm, and the roller temperature is 130° C., to obtain a fluororubber composite material;

[0093] (2) Preparation of composite membrane:

[0094] A 0.3 mm thick carbon fiber polyimide rubber sheet is placed on a 0.6 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the carbon fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 7 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 220°C for 12 hours to obtain a composite diaphragm A4 including a 0.6 mm fluororubber composite material layer, a 0.6 mm PTFE polymer sheet layer, and a 0.3 mm carbon fiber polyimide rubber interlayer located between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0095] Example 5

[0096] (1) Preparation of fluororubber composite materials:

[0097] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0098] (2) Preparation of composite membrane:

[0099] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A5 including a 2 mm fluororubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer located between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0100] Example 6

[0101] The method of Example 5 is used, except that the inorganic filler is 0.5 kg of white carbon black, 1 kg of silicon nitride and 1.1 kg of boron nitride. The specific operation is as follows:

[0102] (1) Preparation of fluororubber composite materials:

[0103] Fluororubber (10 kg of fluororubber 246), inorganic filler (0.5 kg of white carbon black, 1 kg of silicon nitride and 1 kg of boron nitride), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0104] (2) Preparation of composite membrane:

[0105] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A6 including a 1 mm fluororubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer located between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0106] Example 7

[0107] The method of Example 5 was followed, except that the inorganic filler was 1 kg of aluminum silicate and 1.6 kg of diatomaceous earth. The specific operation was as follows:

[0108] (1) Preparation of fluororubber composite materials:

[0109] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of aluminum silicate and 1.6 kg of diatomaceous earth), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C, and the time is 30 minutes; then the obtained product is refined 30 times, the roller distance is 1 mm, and the roller temperature is 140°C, to obtain a fluororubber composite material;

[0110] (2) Preparation of composite membrane:

[0111] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A7 including a 1 mm fluororubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0112] Example 8

[0113] The method of Example 5 was followed, except that no vulcanization accelerator was added. The specific operation was as follows:

[0114] (1) Preparation of fluororubber composite materials:

[0115] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane), mold release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0116] (2) Preparation of composite membrane:

[0117] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A8 including a 1 mm fluororubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0118] Example 9

[0119] The method of Example 5 is used, except that the vulcanization temperature is 190° C. The specific operation is as follows:

[0120] (1) Preparation of fluororubber composite materials:

[0121] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0122] (2) Preparation of composite membrane:

[0123] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 190°C for 16 hours to obtain a composite diaphragm A9 including a 1 mm fluororubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0124] Example 10

[0125] The method of Example 5 is used, except that the thickness of the PTFE polymer sheet is 0.8 mm. The specific operation is as follows:

[0126] (1) Preparation of fluororubber composite materials:

[0127] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0128] (2) Preparation of composite membrane:

[0129] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.8 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm A10 including a 1 mm fluororubber composite material layer, a 0.8 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0130] Comparative Example 1

[0131] The method of Example 5 is used, except that the thickness of the PTFE polymer sheet is 1.5 mm. The specific operation is as follows:

[0132] (1) Preparation of fluororubber composite materials:

[0133] Fluororubber (10 kg of fluororubber 246), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorber (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron oxide red) are added into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C and the time is 30 minutes; then the obtained product is refined 30 times with a roller distance of 1 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0134] (2) Preparation of composite membrane:

[0135] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 1.5 mm thick PTFE polymer sheet, and then the fluororubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm B1 including a 1 mm fluororubber composite material layer, a 1.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer located between the PTFE polymer sheet layer and the fluororubber composite material layer.

[0136] Comparative Example 2

[0137] The method of Example 5 was followed, except that nitrile rubber (purchased from LG Corporation of South Korea, with the brand name LG B3250) was used to replace the fluororubber. The specific operation was as follows:

[0138] (1) Preparation of nitrile rubber composite materials:

[0139] Adding nitrile rubber (10 kg of nitrile rubber), inorganic filler (1 kg of calcium silicate, 1 kg of magnesium silicate, 0.5 kg of calcium carbonate and 0.1 kg of graphite), acid absorbent (0.5 kg of calcium oxide and 0.5 kg of calcium hydroxide), vulcanizing agent (0.01 kg of 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane), vulcanization accelerator (0.01 kg of triallyl isocyanurate), release agent (0.01 kg of paraffin wax) and colorant (0.15 kg of iron red) into a mixer for mixing, wherein the mixing speed is 50 rpm, the temperature is 70°C, and the time is 30 minutes; then refining the obtained product 30 times, with a roller distance of 1 mm and a roller temperature of 140°C, to obtain a nitrile rubber composite material;

[0140] (2) Preparation of composite membrane:

[0141] A 0.4 mm thick ceramic fiber polyimide rubber sheet is placed on a 0.5 mm thick PTFE polymer sheet, and then the nitrile rubber composite material is spread on the ceramic fiber polyimide rubber sheet and thermally bonded at a temperature of 160°C for 10 minutes to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 240°C for 16 hours to obtain a composite diaphragm B2 including a 2 mm nitrile rubber composite material layer, a 0.5 mm PTFE polymer sheet layer, and a 0.4 mm ceramic fiber polyimide rubber interlayer located between the PTFE polymer sheet layer and the nitrile rubber composite material layer.

[0142] Comparative Example 3

[0143] The method of Example 1 is followed, except that the 0.5 mm thick aramid polytetrafluoroethylene composite rubber sheet is not used, and the fluororubber composite material and the PEEK polymer sheet are directly vulcanized.

[0144] (1) Preparation of fluororubber composite materials:

[0145] Fluororubber (10 kg of fluororubber 246), inorganic filler (6 kg of aluminum silicate), acid absorber (1 kg of calcium oxide), vulcanizing agent (0.2 kg of N,N'-biscinnamaldehyde-1,6-hexanediamine), mold release agent (0.02 kg of zinc stearate) and colorant (0.3 kg of colloidal graphite) are added into a mixer for mixing at a speed of 60 rpm, a temperature of 60°C and a time of 15 min; then the obtained product is refined 10 times at a roller distance of 0.2 mm and a roller temperature of 140°C to obtain a fluororubber composite material;

[0146] (2) Preparation of composite membrane:

[0147] The fluororubber composite material was spread on a 0.1 mm thick PEEK polymer sheet and thermally bonded at a temperature of 160°C for 1 min to obtain a pre-vulcanized composite diaphragm. The diaphragm was then vulcanized at 240°C for 8 h to obtain a composite diaphragm B3 including a 0.2 mm fluororubber composite material layer and a 0.1 mm PEEK polymer sheet layer.

[0148] Comparative Example 4

[0149] The method of Example 2 is followed, except that the 0.1 mm thick aramid polyimide rubber sheet is not used, and the fluororubber composite material and the PEEK polymer sheet are directly vulcanized.

[0150] (1) Preparation of fluororubber composite materials:

[0151] Fluororubber (10 kg of fluororubber 26), inorganic filler (0.5 kg of white carbon black, 0.3 kg of calcium silicate, 0.1 kg of magnesium silicate and 0.1 kg of boron nitride), acid absorber (1 kg of magnesium oxide), vulcanizing agent (0.5 kg of N,N'-biscinnamaldehyde-1,6-hexanediamine), mold release agent (0.02 kg of paraffin wax) and colorant (0.2 kg of iron red) are added into a mixer for mixing, wherein the mixing speed is 20 rpm, the temperature is 80°C and the time is 60 min; then the obtained product is refined 20 times with a roller distance of 2 mm and a roller temperature of 100°C to obtain a fluororubber composite material;

[0152] (2) Preparation of composite membrane:

[0153] The fluororubber composite material is spread on a 0.5 mm thick PTFE polymer sheet and thermally bonded at a temperature of 150°C for 10 min to obtain a pre-vulcanized composite diaphragm. The diaphragm is then vulcanized at 180°C for 24 h to obtain a composite diaphragm B4 including a 2 mm fluororubber composite material layer and a 0.5 mm PTFE polymer sheet layer.

[0154] Test Example 1

[0155] The maximum leakage of the composite membranes prepared in the examples and comparative examples was tested, and the results are shown in Table 1. The maximum leakage was measured according to the following method:

[0156] The composite diaphragms A1-A10, B1-B4 prepared in Examples 1-10 and Comparative Examples 1-4 are cut after standing to obtain diaphragms 1a-10a, B1a, B2a, B3a, B4a matching the breathing valve with a nominal diameter of 150 mm, and diaphragms 1b-10b, B1b, B2b, B3b, B4b matching the breathing valve with a nominal diameter of 200 mm. Place it in an environment of 20℃ and 60% humidity for 24h, and test it according to SY / T0511-2010 8.6 leakage test. The specific process is: install the composite diaphragm on the valve disc of the breathing valve with different nominal diameters, and the valve disc weight is 1350Pa. Then install the breathing valve on the breathing valve test platform, adjust the pressure to 1012Pa (0.75 times the opening pressure), measure the leakage of the breathing valve, count the value once every minute, for a total of three times, take the arithmetic mean, that is, the leakage of the tank breathing valve when the pressure is not less than 0.75 times the opening pressure (1012Pa).

[0157] Table 1

[0158]

[0159]

[0160] Test Example 2

[0161] The high temperature resistance of the composite membranes prepared in Examples 1 and 2 and Comparative Examples 3 and 4 was tested, and the results are shown in Table 2. The high temperature resistance was measured according to the following method:

[0162] According to the requirements of GB / T 528-2009, the composite membranes A1 and A2 prepared in Examples 1 and 2 and the composite membranes B3 and B4 prepared in Comparative Examples 3 and 4 were cut into 2-type dumbbell specimens, several in number. The four specimens were placed in an air oven at 80°C, 100°C, and 120°C, respectively, and heated for 48 hours, 96 hours, and 168 hours, and their tensile strength, tensile strength change rate, elongation at break, and elongation at break change rate were tested.

[0163] Table 2

[0164]

[0165]

[0166] As can be seen from Table 1, the breathing valve composite diaphragm is prepared according to the method of the embodiment, and the breathing valve leakage is low; in comparative example 1, the thickness of the PTFE polymer sheet is too thick, and the breathing valve leakage is significantly increased; in comparative example 2, the nitrile rubber is replaced with fluororubber, and the breathing valve leakage is significantly increased; in comparative examples 3 and 4, no fiber composite polymer sheet is used, and the breathing valve leakage is equivalent to that of the embodiment.

[0167] From the results in Table 2, it can be seen that the tensile strength of the composite membrane prepared in Example 1-2 increased from a maximum of 12.5 N / mm to a maximum of 12.5 N / mm under continuous heating at a temperature of 80°C to 120°C for 48h to 168h. 2 Reduced to a minimum of 11.0N / mm 2 , the tensile strength change rate is 0-11.3%, the elongation at break increases from 216% to a maximum of 240%, and the elongation at break change rate increases from 0 to a maximum of 11.1%. The composite membrane prepared in Comparative Examples 3-4 has a tensile strength of 9.7 N / mm at a temperature of 80°C to 120°C and a continuous heating time of 48h to 168h. 2 Reduced to a minimum of 6.3N / mm 2 , the change rate of tensile strength is 1.0% to 25.3%, the elongation at break increases from 234% to a maximum of 292%, and the change rate of elongation at break increases from 0.4 to a maximum of 25.3%. It can be seen that under high temperature conditions, the composite membranes prepared in Examples 1-2 have higher tensile strength and lower elongation at break than the composite membranes prepared in Comparative Examples 3-4, that is, the composite membranes prepared in the examples have better high temperature resistance than the composite membranes prepared in Comparative Examples 3 and 4.

[0168] It can be seen that the composite diaphragm obtained by adopting the technical solution of the present invention has significantly reduced leakage of the breathing valve above 0.75 times the opening pressure of the breathing valve to below the opening pressure, and has excellent high temperature resistance.

[0169] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A three-layer breathing valve composite diaphragm, characterized in that: The composite diaphragm comprises a polymer sheet, a fluororubber composite material layer, and a fiber composite polymer interlayer located between the polymer sheet and the fluororubber composite material layer. Wherein, the thickness of the polymer sheet is 0.1 to 1 mm; The fluororubber composite material layer is prepared from a raw material composition containing fluororubber, inorganic filler, acid absorbent, vulcanizing agent, mold release agent and colorant.

2. The three-layer breathing valve composite diaphragm according to claim 1 is characterized in that: The polymer sheet material forming the polymer sheet layer is selected from one or more of polyetheretherketone, polytetrafluoroethylene and polyimide.

3. The three-layer breathing valve composite diaphragm according to claim 1 or 2, characterized in that: The fiber composite polymer sheet forming the fiber composite polymer interlayer is selected from one or more of aramid polytetrafluoroethylene composite rubber, aramid polyimide rubber, glass fiber polyimide rubber, carbon fiber polyimide rubber and ceramic fiber polyimide rubber; Preferably, the fiber composite polymer interlayer has a thickness of 0.1 to 0.5 mm.

4. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 3, characterized in that: In the raw material composition, the fluororubber is 26-type fluororubber and / or 246-type fluororubber.

5. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 4, characterized in that: In the raw material composition, the inorganic filler is selected from one or more of white carbon black, calcium silicate, magnesium silicate, aluminum silicate, calcium carbonate, barium sulfate, diatomaceous earth, graphite, silicon nitride and boron nitride.

6. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 5, characterized in that: In the raw material composition, the acid absorber is selected from one or more of magnesium oxide, calcium oxide, zinc oxide and calcium hydroxide.

7. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 6, characterized in that: In the raw material composition, the vulcanizing agent is selected from one or more of N,N'-dicinnamaldehyde-1,6-hexanediamine, 2,2-(4-hydroxyphenyl)hexafluoropropane, diisopropylbenzene peroxide and 2,5-dimethyl-2,5-di-tert-butyl peroxide hexane.

8. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 7, characterized in that: In the raw material composition, the release agent is selected from one or more of zinc stearate, ammonium stearate and paraffin.

9. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 8, characterized in that: In the raw material composition, the colorant is selected from one or more of iron red, colloidal graphite and carbon black.

10. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 9, characterized in that: In the raw material composition, the weight ratio of the fluororubber, the inorganic filler, the acid absorber, the vulcanizing agent, the release agent and the colorant is 100:10-60:0.001-20:0.001-5:0.2-2:0.001-3.

11. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 10, characterized in that: The raw material composition also contains a vulcanization accelerator; Preferably, the weight ratio of the fluororubber to the vulcanization accelerator is 100:0.001-2; Preferably, the vulcanization accelerator is selected from benzyltriphenylphosphonium chloride and / or triallyl isocyanurate.

12. The three-layer breathing valve composite diaphragm according to any one of claims 1 to 11, characterized in that: The thickness ratio of the polymer sheet layer to the fluororubber composite material layer is 1:1-4.

13. A method for preparing the three-layer breathing valve composite membrane according to any one of claims 1 to 12, characterized in that: The method includes: (1) kneading the raw material composition, and then refining the obtained product multiple times to obtain a fluororubber composite material; (2) Placing the fiber composite polymer sheet between the polymer sheet and the fluororubber composite material, and then performing thermal bonding and vulcanization to obtain a composite membrane.

14. The method according to claim 13, characterized in that In step (1), the mixing conditions include: temperature of 50 to 80° C., time of 15 to 60 min, and rotation speed of 20 to 60 rpm.

15. The method according to claim 13 or 14, characterized in that In step (1), the refining conditions include: a temperature of 100 to 140° C., a refining frequency of 10 to 30 times, and a roller distance of 0.2 to 4 mm.

16. The method according to any one of claims 13 to 15, characterized in that: In step (2), the thermal bonding conditions include: a temperature of 150 to 160° C. and a time of 1 to 10 minutes.

17. The method according to any one of claims 13 to 16, characterized in that: In step (2), the vulcanization conditions include: temperature of 180 to 240° C. and time of 8 to 24 hours.

18. A three-layer breathing valve composite membrane prepared by the method described in any one of claims 13 to 17.

19. Use of the three-layer breathing valve composite membrane according to any one of claims 1 to 12 or the three-layer breathing valve composite membrane according to claim 18 as a breathing valve sealing material.

Citation Information

Patent Citations

  • Ultra-low temperature resistant fluororubber mixed rubber and preparation method thereof

    CN104045949A

  • A fluororubber material used for sealing members resistant to high temperatures and high pressure and a preparing method thereof

    CN106633544A

  • Flexible ceramizable silicone rubber thermal insulation composite material and preparation method thereof

    CN111761895A

  • Fluororubber for valves and preparation method thereof

    CN115584093A

  • Heat-resistant abrasion-resistant rubber composition and rubber article

    JP1998251471A